PEMENUHAN HAK ATAS INFORMASI PUBLIK DAN PERUBAHAN SOSIAL (STUDI TERHADAP PELAKSANAAN UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK) - Afrizal Tjoetra; Phoenna Ath Thariq; Arfriani Maifizar (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
The fulfillment of the right to public information has not taken place after 10 years of the implementation of Law Number 14 of 2008 concerning Public Information Openness (UU KIP). The research objective is to determine the obstacles and challenges of public agencies in carrying out their obligations and to find out social changes that apply after the implementation of the Public Information Openness Law. This research is qualitative research with a descriptive approach. Data collection relies on various literature related to research topics. The results of the study describe public agencies that have not carried out their obligations due to 4 (four) things, namely the unavailability of data in public agencies, not optimal information management and documentation officials in providing information services, the reluctance of public agencies to be open to the general public and the application of sanctions as a complaint offense. However, the implementation of the Public Information Openness Law has encouraged a social change in society through changes in behavior in public agencies and community.Keywords: Public Information, Public Agency, and Social Change.